Analisis Peranan Diskon Terhadap Minat Pelanggan Berbelanja di Indomaret Kecamatan Medan Maimun - M Jimmy Pamungkas; Yasodra Yasodra; Michelle Sim Aprillia; Devina Devina; Tan Tiam Wi Hendra Wijaya (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
The aim of this study is to see how the discount affects the buyer's desire to shop in Indomaret. To check the relationship between customer purchasing interest and the discounts offered by Indomaret, a linear regression method was used. Results of regression analysis show that, although discounts contribute only a small part of the change in purchasing behavior, there is about 4% of the variation in customer purchasing interests. Quality of service or customer preferences are some additional factors that influence shopping behavior, which should be considered in this study to get a better picture. For further research, it is recommended to conduct a more in-depth customer survey and cover other relevant variables. Advanced research is expected to use this holistic approach to gain a deeper understanding of the variables that affect customer shopping behavior in Indomaret.